Proxy rated quality of life of care home residents with dementia: a systematic review. (16th January 2017) - Robertson, Sarah; Cooper, Claudia; Hoe, Juanita; Hamilton, Olivia; Stringer, Aisling; Livingston, Gill
ABSTRACT: Background: Quality of life (QoL) is an important outcome for people with dementia living in care homes but usually needs to be rated by a proxy. We do not know if relative or paid carer proxy reports differ. We conducted the first systematic review and meta-analysis of data investigating whether and how these proxy reports of QoL differ. Methods: We searched four databases: Medline, Embase, PsychInfo, and CINAHL in October 2015 with the terms: dementia, QoL, proxy, and care home . Included studies either compared proxy QoL ratings or investigated the factors associated with them. We meta-analyzed data comparing staff and family proxy rated QoL. Results: We included 17/105 papers identified. We found no difference between global proxy ratings of QoL ( n = 1, 290; pooled effect size 0.06 (95% CI = −0.08 to 0.19)). Studies investigating factors associated with ratings ( n = 3, 537) found family and staff ratings correlated with the resident's physical and mental health. Staff who were more distressed rated resident QoL lower. Relatives rated it lower when the resident had lived in the care home for longer, when they observed more restraint, or contributed more to fees. Conclusions: Relatives and staff proxy QoL ratings share a clear relationship to resident health and overall ratings were similar. Rater-specific factors were, however, also associated with scores. Understanding why different raters consider the QoL of the same person differently is an important consideration when evaluating the meaning of proxy rated QoL. Proxy raters' backgrounds may affect their rating of QoL.